Combined Activity of Minocycline and Amphotericin B In Vitro Against Medically Important Yeasts - Lew, Michael A. (1978)
The capacity of minocycline to enhance the activity of amphotericin B against Candida albicans, Torulopsis glabrata, Cryptococcus neoformans, and non-albicans Candida was examined in vitro utilizing a time-killing curve technique. Synergism was apparent at 4 h with 5 of 5 strains of C. albicans, 8 of 8 strains of C. neoformans, and 1 of 12 strains of non-albicans Candida. Synergism was apparent at 24 h with the remaining 11 strains of non-albicans Candida and all 5 strains of T. glabrata. C. neoformans was the most susceptible of the yeasts to the minocycline-amphotericin B combination; seven strains showed a 3-log or greater reduction in colony count in 4 h and all strains showed this reduction in 24 h at amphotericin B concentrations of 0.4 μg/ml or less in the presence of minocycline.